UTILIZING MIND MAPPING MODEL TO IMPROVE STUDENTS’ LEARNING OUTCOMES AT GRADE 4 SD N 02 MEGAWON KUDUS - Mayalinda Siska Harwanti; Ika Ari Pratiwi; Deka setiawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This classroom action research was carried out at grade IV SD N 02 Megawon involving 25 students. This research was conducted for two cycles; each cycle consisted of four stages, namely planning, implementation, observation, and reflection. The independent variable in this study was Mind Mapping model while the dependent variable was learning outcomes. The data were analyzed quantitatively and qualitatively. The results showed that Mind Mapping model improve the students’ learning outcomes on theme 5. It was found that the percentage of learning outcomes in cycle I was 40% and it increased in cycle II to 60%. Then, the percentage of students’ activity in cycle I was 80% with good criteria and increased in cycle II to 95%. This increase was supported by the teachers’ skills to manage the first cycle of learning with a percentage of 76.78% and increased in the second cycle to 83.9%. Thus, Mind Mapping model improved students’ learning outcomes on theme 5 at grade IV SD N 02 Megawon.